METHODOLOGICAL ASPECTS OF DETERMINING LEVELS OF DANGEROUS AND NUISANCE EFFECTS OF ROLLING STOCK ON THE OPERATION OF TRACK CIRCUITS - Zavhorodniy, O. V.; Havryliuk, V. I.; Sychenko, V. H. (Science and Transport Progress, 2005)
An analysis of electromagnetic influence of rolling stock and traction power supply system on rail circuits and cab locomotive signalization has been provided. A method of determining permissible levels of dangerous and preventing electromagnetic influence of traction current on railway circuits and cab locomotive signalization has been proposed.